Shakespeare, "Macbeth" and the Hindu Nationalism of Nineteenth-Century Bengal - Sarkar, Abhishek (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
The essay examines a Bengali adaptation of Macbeth, namely Rudrapal Natak (published 1874) by Haralal Ray, juxtaposing it with differently accented commentaries on the play arising from the English-educated elites of 19th Bengal, and relating the play to the complex phenomenon of Hindu nationalism. This play remarkably translocates the mythos and ethos of Shakespeare’s original onto a Hindu field of signifiers, reformulating Shakespeare’s Witches as bhairavis (female hermits of a Tantric cult) who indulge unchallenged in ghastly rituals. It also tries to associate the gratuitous violence of the play with the fanciful yearning for a martial ideal of nation-building that formed a strand of the Hindu revivalist imaginary. If the depiction of the Witch-figures in Rudrapal undercuts the evocation of a monolithic and urbane Hindu sensibility that would be consistent with colonial modernity, the celebration of their violence may be read as an effort to emphasize the inclusivity (as well as autonomy) of the Hindu tradition and to defy the homogenizing expectations of Western enlightenment